Determinisme Soeharto dan Masa Depan Orde Baru - Eep Saefullah Fatah (Studia Islamika, 1997)
Leadership and Culture is a collection of Liddle's articles which had been published in some journal and books. Written over the course of 1984-1993, these article were classified into two main themes. The first theme consists of four articles, is designed to look at the future of this regime, especially in its relationship with the changing political climate and the agenda of democratization.DOI: 10.15408/sdi.v4i2.784